Implementation of the Flipped Classroom Learning Model for Reading Procedure Text Material during the COVID-19 - Al Hakim, Adam (The Indonesian Institute of Science and Technology Research, 2023)
The objectives of this research are to apply the procedures used in the implementation of the flipped classroom model in learning English reading skills to the procedure text material for 11th-grade students at SMA Muhammadiyah 1 Yogyakarta due to the pandemic situation of Covid-19 disease and to find out what activities are used in the implementation of the flipped classroom model in learning English reading skills on procedure text material for 11th-grade students at SMA Muhammadiyah 1 Yogyakarta due to the pandemic situation of Covid-19 disease. This research is based on action research. Action research is a reflective method aimed at resolving a specific teaching-learning issue that has been discovered. This research was conducted for 11th-grade students at SMA Muhammadiyah 1 Yogyakarta. The number of students in one classroom was 33, each with a background for each student. As a result, it can be seen that using the Flipped Classroom learning model generally has a very positive impact on improving students' reading ability, particularly in procedural text.